Solar remote monitoring unit - Omar, M.; Qaiser, M.; Usman, M.; Tajamal, K.; Larkin, S.; Raw, B.; Khan, S. (International Journal of Engineering and Technology, 2022)
In this manuscript, a smart, IoT-enabled, solar-based datalogger, which can measure AC and DC voltage and current of solar panel accurately is presented. Combination of stand-alone current and voltage sensors are used to measure to develop the datalogger. The datalogger can measure the current non-invasively, without introducing disturbance to the circuit under test. The PCB is fabricated, and measurements have been made to evaluate the system's performance. The results demonstrate that sensed values give maximum accuracy compared to manually tested values. The main purpose of the study is to measure the electrical parameters of solar panels to achieve maximum accuracy, reducing the error rate, thus causing a reduction in electricity bills, and accessing the data remotely. The system can send data to the cloud so that a remote user can check the data through a web-application.